MOTIVASI KERJA GURU DI SEKOLAH DASAR NEGERI GUGUS 2 KECAMATAN TANJUNG BARU KABUPATEN TANAH DATAR - Dian Handayani (Jurnal Bahana Manajemen Pendidikan, 2015)
Phenomena in the field suggests that motivation of teacher working in a state that has not been ideal. This study aimed to obtain information about  motivation of teacher working in elementary school gugus 2 kecamatan tanjung baru Kabupaten tanah datar. This descriptive type of research. The population in this study were all teachers in elementary school negeri gugus 2 kecamatan tanjung baru kabupaten tanah datar Barattotaling 45 people. The sample size is determined by the table krejchi and gained as much as 40 people. Sampling technique using proportionate stratifed random sampling technique. The research instrumen was a questionnaire likert scale models that have been tested for validity and reliability. In general, motivation of teacher wirking in elementary school gugus 2 kecamatan tanjung baru kabupaten tanah datar well in the category with an average score of 4.35. Thus it can be said that the work motivation is good.Key word :motivation of teacher working